Challenges faced by supply chain management officials in terms of implementing the procurement process at the Department of Agriculture and Rural Development in Waterberg, Vhembe and Mopani Districts - Makgaleng, Manee Lucia (My University, 2022)
The purpose of this study was to investigate challenges faced by Supply Chain Management (SCM) officials in the implementation of the procurement process at the Limpopo Department of Agriculture and Rural Development in Sekhukhune and Capricorn District as per the approval by TREC. The researcher requested the Head of Department for the Limpopo Department of Agriculture and Rural Development to grant approval to conduct the study at Sekhukhune and Capricorn Districts. The Head of Department delegated the Departmental Research Committee to attend to the researcher’s request. The Departmental Research Committee advised the researcher and granted approval to conduct the study at Waterberg, Mopani and Vhembe District offices, since the researcher is working at Sekhukhune District sharing the same complex with Capricorn District office. A qualitative research method was used to collect data which was collected using structured interview questions. Participants in the study were officials working at Waterberg and Vhembe District. The researcher was unable to conduct research at Mopani District due to the unavailability of the participants. The findings revealed that SCM officials are not adequately trained but are still expected to deliver service efficiently and effectively. The study further revealed that there is a shortage of staff and SCM officials are struggling to deliver because of IT Infrastructure network problems. It was concluded that SCM Practitioners are facing some challenges in the implementation of the procurement process at Limpopo Department of Agriculture and Rural Development in Waterberg and Vhembe District offices. The respondents indicated that there is a shortage of staff and also that posts which are vacant are not given priority. In addition, the IT Infrastructure Network problem was a big challenge to SCM Practitioners since they are without network most of the time while their systems require daily network access. The research indicated that officials are not well trained and that there is lack of communication between the districts and Head office. It is recommended that vacant posts be filled immediately after the post becomes vacant and that the Department should develop a communication tool which will be circulated to all SCM officials. Management at head office is advised to arrange iv monthlymeetingsanda SCM forum inviting all SCM officials starting from the lower level upwards to address challenges and update each other about the new developments within the Unit. It is recommended that the Department of Agriculture and Rural Development introduce intensive Training programmes within the Department to ensure that SCM Practitioners remain well informed. It is also recommended that the Department of Agriculture and Rural Development make a concerted effort to train top management in order to solicit their full support to the districts. It is recommended that the Department develops its SCM policy. The Department is advised to install Wi-Fi to officials working for the Limpopo Department of Agriculture and Rural Development at all five Districts in order to promote effective and efficient service delivery. It is recommended that the Department should allocate all necessary Logis training to SCM officials before they get access to the system. The Department needs to work with Provincial Treasury on the allocation of the items which need to be procured e.g seed and seedling in order to speed up service delivery. It is recommended to the Department to appoint well qualified and experienced SCM officials to fill vacant posts, to offer training to officials who are already within the Unit and provide Bursaries to SCM officials to acquire long-term qualifications such as Diplomas and Degrees.
Thesis (MBA) -- University of Limpopo, 2022
Keywords: IT Infrastructure; Provincial Treasury; Rural Development; Supply chain management; Procurement process; Business logistics -- Management; Physical distribution of goods -- Management; Procurement; Purchasing -- Management; Government employees